ASSOCIATION OF THE SEH GENE PROMOTER POLYMORPHISMS AND HAPLOTYPES WITH PREECLAMPSIA: Association of the EPHX2 promoter polymorphisms and preeclampsia - Sarı, İsmail (Journal of Medical Biochemistry, 2020)
Background: The epoxyeicosatrienoic acids (EETs) have antihypertensive, anti-inflammatory, and organ protective properties, and their circulation levels are related to hypertension, diabetes mellitus, cardiovascular diseases, and preeclampsia. Soluble epoxide hydrolase (sEH) catalyzes the degradation of EETs to less biologically active dihydroxyeicosatrienoic acids. Here we sequenced the promoter region of EPHX2 to investigate the association between promoter sequence alterations that we thought to affect the expression levels of the enzyme and preeclampsia (PE). Methods: Nucleotide sequencing of the promoter region of the EPHX2, spanning from position −671 to +30, was performed on 100 pregnant women with PE and, 20 or more weeks pregnant normotensive, healthy women (n=100) Results: Pregnant women who carry rs4149235, rs4149232, rs73227309, and rs62504268 polymorphisms have 4.4, 2.4, 2.3, and 2.8 times significantly increased risk of PE, respectively. CCGG (OR: 3.11; 95% CI: 1.12-8.62) and CCCA (OR: 0.45; 95 % CI: 0.36-0.55) haplotypes were associated with an increased and decreased risk of PE, respectively. Conclusions: Four SNPs (rs4149232, rs4149235, rs73227309, and rs62504268) in the promoter region of the EPHX2, and CCGG and CCCA haplotypes of these 4 SNPs were significantly associated with PE. These SNPs in the promoter region may affect sEH expression and thus enzyme activity and may play a role in PE pathogenesis by causing individual differences in EET levels. However, future studies are needed to confirm our findings and examine the effect of these SNPs on the sEH expression and/or enzyme activity.